Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I want to evaluate this integral:


The book only says to integrate by parts $\int{\dfrac{1}{(x^2+2px+q)^{n-1}}dx}$, for simplicity if $n = 2$ I get: $\int{\dfrac{1}{(x^2+2px+q)}dx}=\dfrac{x}{x^2+2px+q}+\int{\dfrac{2x^2+2px}{(x^2+2px+q)^2}}dx$.

Now I don't know what to do.

share|cite|improve this question
up vote 2 down vote accepted

To answer your specific question, here is a trick that will work. Note that $$2x^2+2px=(2x^2+4px+2q)-2px-2q=(2x^2+4px +2q)-p(2x+2p)-2q+2p^2.$$ It follows that $$\int \frac{dx}{x^2+2px+q}=\frac{x}{x^2+2px+q} +2\int \frac{x^2+2px+q}{(x^2+2px+q)^2}\,dx -p\int \frac{2x+2p}{(x^2+2px+q)^2}\,dx+ (2p^2-2q)\int \frac{dx}{(x^2+2px+q)^2}.$$ On the right, the first integral is just the integral on the left. The second integral yields to the substitution $u=x^2+2px+q$. And the third integral is the one we wanted to evaluate. So we can express $\int \frac{dx}{(x^2+2px+q)^2}$ in terms of $\int \frac{dx}{x^2+px+q}$ except in the case $p^2=q$. But in that case $(x^2+2px+q=(x+p)^2$, and the integration is easy without going through the integration by parts.

It would have been easier to make the immediate substitution $x+p=y$, but I wanted to carry on from the point you had reached.

What follows is the beginning of much longer answer I had typed. The reduction formula got unpleasant to work with, so below is only the beginning of that answer.

We have $ax+b=\frac{a}{2}(2x+2p)+ b-ap$. So our integral is $$\frac{a}{2}\int \frac{2x+2p}{(x^2+2px+q)^n}\,dx+ (b-ap)\int \frac{dx}{(x^2+2px+q)^n}.\tag{$1$}$$ The first integral in $(1)$ is found by making the substitution $u=x^2+2px+q$. So we are integrating a power of $u$, easy.

The second integral in $(1)$ is not so easy! We use, repeatedly if necessary, a Reduction Formula (they are discussed in great detail in Wikipedia).

For any positive integer $n$, let $$I_n=\int \frac{dx}{(x^2+2x+q)^n}.$$ We show how to find a general expression for $I_n$ in terms of $I_{n-1}$. Thus if we start with for example $n=3$, we express $I_3$ in terms of $I_2$, then $I_2$ in terms of $I_1$.

Finally, $I_1$ breaks up into cases. Complete the square to get $x^2+2px+q=(x+p)^2+q-p^2$. If $q-p^2=0$, we had an easy integral to begin with, and the Reduction Formula was a waste of time. If $q-p^2\gt 0$, a substitution brings us to $\int \frac{1}{u^2+1}$. If $q-p^2\lt 0$, use partial fractions.

Now we begin the reduction. As in what you did, we use integration by parts. It is easier for me to go backwards. So we calculate $I_{n-1}$ using integration by parts. Let $n\ge 2$. We have $$I_{n-1}=\int \frac{dx}{(x^2+2px+q)^{n-1}}.$$ Let $u=\frac{1}{(x^2+2px+q)^{n-1}}$ and let $dv=dx$. Then $du=-\frac{(n-1)(2x+2p)}{(x^2+2px+q)^n}$ and we can take $v=x$. So $$I_{n-1}= \frac{x}{(x^2+2px+q)^{n-1}}+(n-1)\int \frac{2x^2+2px}{(x^2+2px+q)^{n}}\,dx.$$ To finish, use the same trick as the one at the beginning of the post. However, you will find the calculation far more pleasant with the preliminary change of variable $y=x+p$.

share|cite|improve this answer

1.for the integrand $\dfrac{1}{x^2+2px+q}$ complete the square to get

2.then substitute $u=p+x$

3.factor out $\dfrac{1}{4}(4q-4p)^2$

The integral reduced to simple trigonometric function

share|cite|improve this answer
Do you have a typo in 1? How do you complete the square in $\dfrac{1}{x^2+2px+q}$ to get $\dfrac{4}{(4q-4p)^2+(p+x)^2}$? – Américo Tavares May 21 '13 at 11:32

General description. A partial fraction of the form $$\dfrac{Bx+C}{\left[ \left( x-r\right) ^{2}+s^{2}\right] ^{n}}$$ is integrable by substitution, using the change of variables $x=r+st$. With this method an integral of the form

$$\displaystyle\int \frac{Bx+C}{\left[\left( x-r\right) ^{2}+s^{2}\right] ^{n}}dx\tag{1}$$

is transformed into an integral of the form

$$\displaystyle\int \frac{Dt+E}{(t^{2}+1)^{n}}dt=D\int \frac{t}{(t^{2}+1)^{n}} dt+E\int \frac{1}{(t^{2}+1)^{n}}dt\tag{2}.$$

The first integral is a table integral. The second one satisfies a recurrence relation.

Application to the given integral. Rewrite the integrand as $\dfrac{ax+b}{\left[(x+p)^{2}+q-p^{2}\right]^{n}}$ and make the substitution $$ \begin{equation*} x=-p+\sqrt{q-p^{2}}\, t.\tag{3} \end{equation*} $$ Then $$ \begin{eqnarray*} I &=&\int \frac{ax+b}{(x^{2}+2px+q)^{n}}dx=\int \frac{ax+b}{ \left[(x+p)^{2}+q-p^{2}\right]^{n}}dx, \tag{4}\\ && \\ \\ M &=&a\sqrt{q-p^{2}},\quad N=b-ap,\quad K=\frac{\sqrt{q-p^{2}}}{\left( q-p^{2}\right) ^{n}} \\ \\ && \\ I &=&K\int \frac{M}{(t^{2}+1)^{n}}t+\frac{N}{(t^{2}+1)^{n}}dt, \\ &=&KM\int \frac{1}{(t^{2}+1)^{n}}tdt+KN\int \frac{1}{(t^{2}+1)^{n}}dt \\ &=&-\frac{KM}{2(n-1)}\frac{1}{(t^{2}+1)^{n-1}}+KN\int \frac{1}{(t^{2}+1)^{n}} dt.\tag{5} \end{eqnarray*} $$ The last integral can be split into two, the latter being integrable by parts which generates the recursive relation $(6)$ bellow. For $n\ne 1$, we have: $$ \begin{eqnarray*}I_n&=& \int \frac{1}{(t^{2}+1)^{n}}dt =\int \frac{1+t^{2}-t^{2}}{(t^{2}+1)^{n}} dt\\ &=&\int \frac{1}{(t^{2}+1)^{n-1}}dt-\int \frac{t^{2}}{(t^{2}+1)^{n}}dt \\ &=&\int \frac{1}{(t^{2}+1)^{n-1}}dt+\frac{t}{2(n-1)\left( t^{2}+1\right) ^{n-1}} \\ &\qquad - &\frac{1}{2(n-1)}\int \frac{1}{\left( t^{2}+1\right) ^{n-1}}\,dt \\ &=&\frac{t}{2(n-1)\left( t^{2}+1\right) ^{n-1}}+\frac{2n-3}{2(n-1)}\int \frac{1}{\left( t^{2}+1\right) ^{n-1}}\,dt\\ &=&\frac{t}{2(n-1)\left( t^{2}+1\right) ^{n-1}}+\frac{2n-3}{2(n-1)}I_{n-1}.\tag{6} \end{eqnarray*} $$

For $n=1$ $$ I_1=\int \frac{1}{t^{2}+1}dt=\arctan t+\text{Constant}.\tag{7} $$

ADDED. For the particular case $n=2$, we get from $(6),(7)$ $$ \begin{eqnarray*} I_2=\int \frac{1}{(t^{2}+1)^{2}}dt &=&\frac{1}{2}\frac{t}{t^{2}+1}+\frac{1}{2}I_1 \\ &=&\frac{1}{2}\frac{t}{t^{2}+1}+\frac{1}{2}\arctan t+\text{Constant}.\tag{6$\mathrm{a}$} \end{eqnarray*} $$

and from $(5)$

$$ \begin{eqnarray*} I &=&\int \frac{ax+b}{(x^{2}+2px+q)^{2}}dx \\ &=&-\frac{a}{2}\frac{1}{x^{2}+2px+q}+\frac{b-ap}{2\left( q-p^{2}\right) } \frac{x+p}{q+x^{2}+2xp}\\ &+& \frac{b-ap}{2\left( q-p^{2}\right) ^{3/2}}\arctan \frac{x+p}{\sqrt{q-p^{2}}}+\text{Constant}. \end{eqnarray*}\tag{5$\mathrm{a}$} $$

Setting $a=0,b=1$ in $(5\mathrm{a})$ we evaluate your last integral for $q>p^2$:

$$ \boxed{\begin{eqnarray*} \int \frac{1}{(x^{2}+2px+q)^{2}}dx&=&\frac{1}{2\left( q-p^{2}\right) }\frac{x+p}{x^{2}+2px+q}\\&+&\frac{1}{2\left( q-p^{2}\right) ^{3/2}}\arctan \frac{x+p}{\sqrt{q-p^{2}}}+\text{Constant}. \end{eqnarray*}} $$ $$\tag{5$\mathrm{b}$}$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.